Scholarly Achievement versus Editorial Board Membership. The Case of the Top Ten Polish Pedagogical Journals - Rębisz, Sławomir (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2021)
An invitation to become an editorial board member (EBM) of an academic journal should be regarded as evidence of recognition of a scholar’s research achievement and impact on his discipline. This is a requirement of Merton’s norm of universalism in science, which proposes that awards and prestige ought to be held to objective and pre-established impersonal criteria that depend exclusively on the quality of scholarly output. This principle is particularly important in the context of editorial teams of academic journals. The aim of this paper is to present an empirical case study of the academic achievements of the EBMs of the top ten Polish pedagogical journals, in 2020. For research purposes, the author assumed that the criterion for nomination to the editorial board was the scholars’ output, as evidenced by their publications indexed in the WoS and Scopus databases and also the number of corresponding citations. The results put into question the idea that the editorial nominations examined were indeed grounded in the publications indexed in the WoS and Scopus databases. Based on the record of EBMs output indexed in these databases, most EBMs analysed were not proven to be the most productive or cited scholars.